The immunomodulatory effect of Neem (Azadirachtaindica) seed aqueous, ethanolic extracts and Candida albicans cell wall mannoproteins on immune response in mice vaccinated with Brucella Rev-1: Tareq J. Faal ,Adhia, A. Hussein ,Mohammad K Faraj and Al-Ramahy A.K - Faal, Tareq J. (The Iraqi Journal of Veterinary Medicine, 2012)
In the present study, the immunomodulatory effect of Neem (Azadirachtaindica)seed aqueous, ethanolic extracts and Candida albicans cell wall mannoproteins on theimmune response of mice vaccinated with Brucella Rev-1 vaccine was investigated. Thestudy was conducted on two main groups(160 mice for each group), Each group wasdivided into eight subgroups 20 mice for each (I: treated with distilled water, II: treatedwith the Brucella Rev-1 vaccine, III: treated with mannoproteins, IV: treated with neemaqueous extract, V: treated with neemethanolic extract, VI, VII and VIII: treated withmannoproteins, neem aqueous extract and neemethanolic extract, respectively, then theywere vaccinated with Brucella Rev-1). All these treatments were carried out on day 1and then vaccinated with brucella Rev-1 vaccine on day 4 .Then the mice were tested asfollows , on day 8 after vaccination(serum IFN-γ level), day 21 for (anti-Brucellaantibody titer). The doses of both plant extracts and mannoproteins represented 10% ofthe calculated LD50 (neem extracts: 3.8096 g/Kg mannoproteins: 5.7144 mg/Kg), whichwere given subcutaneously. Mice of the second main group were injected with theimmune suppressive drug prednisolone (5mg/Kg) 5 days prior to the treatments, whichcarried out on mice of the first main group. The results demonstrated clearimmunomodulatory effects (improvement of non-specific, humoral immunity) of thetested immunomodulators in mice vaccinated with Brucella Rev-1 as compared withmice that were not treated with Neem extracts or mannoproteins. In this regard, Theinterferon-γ showed a significant increase (P≤ 0.01) serum level in immunomodulatortreatedand -vaccinated mice in comparison with negative and positive groups, and againgroup VII showed the highest increase. The anti-Brucella antibodies assessed by indirectImmunoflourescent test also showed a significant increase titer in immunomodulatortreatedand -vaccinated mice in comparison with negative and positive groups .Conclusion: The aqueous and ethanolicNeem seed extract reported the highestenhancement in all immunological parameters employed in comparison withmannoproteins of Candida albicans cell wall.